Convergence in the domains of static spatial relations and events of putting and taking. Evidence from bilingual speakers of Romansh and German - Berthele, Raphael (International journal of bilingual education and bilingualism, 2015)
In this article the way bilinguals handle differing semantic categories in their two languages will be investigated. Drawing on bilingual data from multilingual speakers of Romansh as well as from speakers of (Swiss) German, the tensions that emerge from 'conflicting habits' in the two languages are analyzed in the semantic domain of spatial relations. A particular focus will lie on spatial categories that differ across the two languages, e.g. the regular usage of several different verbs of putting in German vs. one general verb in Romansh. The analyses show differing degrees and different ways of reducing these tensions (convergence) in the bilingual subjects. Data from the domain of putting and taking events are analyzed, and multiple comparisons (cross-linguistic between speakers, cross-linguistic within speakers, variation in the responses to individual stimuli, etc.) are carried out. Measures of consensus vs. dissent are presented, allowing for comparisons of semantic categories, languages, and idiolects.